Near-Edge X-Ray Absorption Fine Structure of Ultrananocrystalline Diamond/Hydrogenated Amorphous Carbon Films Prepared by Pulsed Laser Deposition. (7th June 2009) - Ohmagari, Shinya; Yoshitake, Tsuyoshi; Nagano, Akira; AL-Riyami, Sausan; Ohtani, Ryota; Setoyama, Hiroyuki; Kobayashi, Eiichi; Nagayama, Kunihito
Abstract : The atomic bonding configuration of ultrananocrystalline diamond (UNCD)/hydrogenated amorphous carbon (a-C:H) films prepared by pulsed laser ablation of graphite in a hydrogen atmosphere was examined by near-edge X-ray absorption fine structure spectroscopy. The measured spectra were decomposed with simple component spectra, and they were analyzed in detail. As compared to the a-C:H films deposited at room substrate-temperature, the UNCD/a-C:H and nonhydrogenated amorphous carbon (a-C) films deposited at a substrate-temperature of 550 ∘ C exhibited enhanced π ∗ and σ ∗ C ≡ C peaks. At the elevated substrate-temperature, the π ∗ and σ ∗ C ≡ C bonds formation is enhanced while the σ ∗ C–H and σ ∗ C–C bonds formation is suppressed. The UNCD/a-C:H film showed a larger σ ∗ C–C peak than the a-C film deposited at the same elevated substrate-temperature in vacuum. We believe that the intense σ ∗ C–C peak is evidently responsible for UNCD crystallites existence in the film.